Pre-schoolers’ behavioural and emotional problems during the first quarantine due to COVID-19 pandemic: The role of parental distress and screen time - Rakickienė, Lauryna; Jusienė, Roma; Baukienė, Edita; Breidokienė, Rima (Psichologija, 2021)
Lithuania was one of the countries that applied quarantine during the rise of COVID-19 pandemic in spring 2020, the duration of which was three months (from March 16th, 2020 to June 16th, 2020). Despite emerging literature showing negative effects of quarantine on children’s mental health, insight into specific risk factors is lacking due to limited longitudinal data. The aim of the present study was to analyse changes in Lithuanian pre-schoolers’ emotional and behavioural problems during the first quarantine due to COVID-19 pandemic and their relations to the potential risk factors such as parental distress and increase in daily screen time. Parents of 78 children aged 4 to 6 (31% girls and 69% boys, mean age at the first measurement 66.1 months (SD = 10.33)) completed Child Behaviour Checklist (CBCL/1½-5), questions on children’s screen time and physical activity and reported their distress before the quarantine (November 2019–February 2020) and at the end of it (May–June 2020). Results showed that children had more behavioral problems, spent more time on screens and were less physically active during the quarantine, and their parents were experiencing more distress than before. However, parental distress emerged as the only variable that predicted preschoolers’ emotional and behavioral problems during the quarantine after a child’s previous problems were taken into account. This highlights the importance of targeting support towards families raising children with behavioral problems, as the challenges they were already facing increase during quarantine and their parents may be more susceptible to less desirable practices such as providing children with more screen time as a way to cope with this situation.